Cost-Effectiveness of Gliclazide-Based Intensive Glucose Control vs. Standard Glucose Control in Type 2 Diabetes Mellitus. An Economic Analysis of the ADVANCE Trial in Vietnam - Nguyen-Thi, Hai-Yen; Nguyen, Nga TQ.; Le, Nguyen Dang Tu; Beillat, Maud; Ethgen, Olivier (Frontiers in Public Health, 2020)
Introduction: ADVANCE was a large, multinational clinical study conducted over 5 years in type 2 diabetes mellitus (T2DM). In all, 11,140 patients were randomly assigned to receive gliclazide-based intensive glucose control (IGC) or standard glucose control (SGC). IGC was shown to significantly reduce the incidence of major macrovascular and microvascular events (composite endpoint) or major microvascular events compared with SGC, primarily by enhancing renal protection. We assessed the cost-effectiveness of IGC vs. SGC, based on the ADVANCE results, from a Vietnamese healthcare payer perspective. Materials and Methods: A partitioned survival times model across five health states (no complications, myocardial infarction, stroke, end-stage renal disease [ESRD], and diabetes-related eye-disease) was designed. Time-to-event curves were informed by the cumulative incidence of events and corresponding hazard ratios from the ADVANCE study. Health outcomes were expressed in terms of ESRD avoided and quality-adjusted life years (QALYs). Costs (in US ) comprised treatment costs and health state costs. Utility weights and costs were documented from literature reporting Vietnamese estimates. For sensitivity analyses, all parameters were individually varied within their 95% confidence interval bounds (when available) or within a ±30% range. Results: Over a 5-year horizon, IGC avoided 6.5 additional ESRD events per 1,000 patients treated compared with SGC (IGC, 3.5 events vs. SGC, 10.0 events) and provided 0.016 additional QALYs (IGC, 3.570 QALYs vs. SGC, 3.555 QALYs). Total costs were similar for the two strategies (IGC, 3,786 vs. SGC, 3,757). Although the total drug costs were markedly higher for IGC compared with SGC (1,703 vs. 873), this was largely offset by the savings from better renal protection with IGC (IGC, 577 vs. SGC, 1,508). The incremental cost-effectiveness ratio (ICER) of IGC vs. SGC was 1,878/QALY gained, far below the threshold recommended by the World Health Organization (i.e., 1–3 × gross domestic product per inhabitant ≈7,500 in Vietnam). The ICER of IGC vs. SGC per ESRD event avoided was 4,559/event. The findings were robust to sensitivity analysis. Conclusion: In Vietnam, gliclazide-based IGC was shown to be cost-effective compared with SGC from a healthcare payer perspective, as defined in the ADVANCE study.